2018
DOI: 10.7567/jjap.57.028001
|View full text |Cite
|
Sign up to set email alerts
|

In-situ X-ray diffraction reveals the degradation of crystalline CH3NH3PbI3 by water-molecule collisions at room temperature

Abstract: We have developed a vacuum-compatible chamber for in-situ X-ray diffraction (XRD) studies and have used it to characterize the changing crystal structure of an inorganic-organic hybrid perovskite material, CH 3 NH 3 PbI 3 (MAPbI 3 ), during interactions with water vapor at room temperature. In the XRD spectra, we have observed the degradation of MAPbI 3 and the creation of MAPbI 3 hydrates, which follow simple rate equations. The time constant for the degradation of MAPbI 3 during accelerated aging suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The diffraction peaks of 14.17 and 28.5° are assigned to the (110) and (220) lattice planes of the perovskite phase, respectively, and are indicated by stars in Figure c,d. Two other peaks appear at 13.81 and 27.69° for the nonperovskite phase and are indicated by ☆ . Further increasing the substrate temperature results in the emergence of perovskite phases with strong XRD diffraction peaks for all the samples and a gradual decrease in the nonperovskite phase content.…”
Section: Resultsmentioning
confidence: 89%
“…The diffraction peaks of 14.17 and 28.5° are assigned to the (110) and (220) lattice planes of the perovskite phase, respectively, and are indicated by stars in Figure c,d. Two other peaks appear at 13.81 and 27.69° for the nonperovskite phase and are indicated by ☆ . Further increasing the substrate temperature results in the emergence of perovskite phases with strong XRD diffraction peaks for all the samples and a gradual decrease in the nonperovskite phase content.…”
Section: Resultsmentioning
confidence: 89%
“…Previously, we reported the degradation processes of MAPbI 3 using in situ XRD measurements. 22 We have revealed the number of collisions required between the MAPbI 3 lattice and water molecules to induce the degradation reaction. In the present study, we determined the activation energy of the degradation process of MAPbI 3 caused by interaction with water molecules from the temperature dependence of the in situ XRD measurements.…”
mentioning
confidence: 95%
“…( 1)] is the most important for the loss of power-conversion efficiency. Our previous study 22 reported that the rate constant (s 1 ) of the chemical reaction in Eq. ( 1) was 18 min at a temperature of 26 C and that multiple collisions (1/g ¼ 1.8 Â 10 9 , where g is the collision yield) between the water molecules and crystalline MAPbI 3 are required to degrade the material.…”
mentioning
confidence: 99%